1983
DOI: 10.1093/auk/100.2.425
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Growth Patterns of Three Tropical Bird Species

Abstract: Energy budgets and growth data are presented for nestlings of three species of tropical insectivores: White-bellied Swiftlets (Collocalia esculenta), Blue-throated Bee-eaters (Merops viridis), and Pacific Swallows (Hirundo tahitica). A comparison with temperate nestlings, matched for body size, shows that the peak energy demand in our tropical sample averaged around 60% of temperate counterparts. We attribute savings to slow growth rates, reduced thermoregulatory requirements, a low resting metabolism (in swal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…The calculated optimum values of K for representative values of variables, which are reasonable for temperate-zone passerine birds, are well within the range of observed values for growth rates of these species. Ricklefs (1976) and Bryant and Hails ( 1983) found that standard metabolic rates of nestlings were lower in some tropical passerines than in temperate passerines, a parallel result for adults having been reported by Weathers (1979) and Hails (1983) (but see Vleck and Vleck [1979] for contrary data). In addition, large increases in nesting mortality rate result in only a small increase in optimum growth rate.…”
Section: Kn+• Kn Ubmentioning
confidence: 53%
“…The calculated optimum values of K for representative values of variables, which are reasonable for temperate-zone passerine birds, are well within the range of observed values for growth rates of these species. Ricklefs (1976) and Bryant and Hails ( 1983) found that standard metabolic rates of nestlings were lower in some tropical passerines than in temperate passerines, a parallel result for adults having been reported by Weathers (1979) and Hails (1983) (but see Vleck and Vleck [1979] for contrary data). In addition, large increases in nesting mortality rate result in only a small increase in optimum growth rate.…”
Section: Kn+• Kn Ubmentioning
confidence: 53%
“…1980. A parallel pattern of slow growth and fat accumulations was found by Bryant and Hails ( 1983) in insectivorous birds faced with an unpredictable food supply. The fat accumulations and slow growth (reduced daily energy requirement) exhibited by all these birds will undoubtedly function to the benefit of the chick during especially long fasts, but have these characteristics evolved specifically as adaptations to intermittent feeding?…”
Section: Payload Mass and The Chick's Swallowing Capacity-mentioning
confidence: 64%
“…The maximum energy demand placed on parents by altricial young, a parameter that may have implications for brood productivity (Bryant & Hails 1983) and that ultimately is related to fitness, may occur toward the end of the nestling period (but see Weathers & Sullivan 1989). If a relationship between peak energy demand and brood productivity does exist, then interspecific variation in peak daily metabolizable energy intake of nestlings should provide clues about the capacity of parents to find food in a given environment, and how natural selection has modulated growth rates and clutch size to maximize fitness.…”
Section: Discussionmentioning
confidence: 99%